What drives the evolution of Corporate Social Responsibility strategies? An institutional logics perspective. (10th January 2018) - Arena, M.; Azzone, G.; Mapelli, F.
Abstract: This paper moves from the idea that the term Corporate Social Responsibility (CSR) refers to an "umbrella" concept entailing a diversified set of practices through which a company aims to meet the expectations of a broad range of stakeholders. This concept implies that there is a need for companies to disentangle the complex relationships among their social obligations and to define CSR strategies that are actually effective and efficient. Therefore, this paper aims to identify the dimensions along which CSR is evolving and the pressures that can explain companies' positioning in relationship to these dimensions in order to provide managers and academics with a comprehensive framework. Grounded on an institutional perspective and specifically on the concept of institutional logics, a framework of the contextual factors that influence companies' choices with respect to CSR strategies is developed. The proposed framework is then used to analyse the case of a multinational energy company that has significantly redefined its CSR strategy over time, thus tracing the influence of different institutional pressures. The case analysis illuminated three main types of responses to tensions emerging between different pressures: focusing on one prevailing logic; hybridizing practices to balance contrasting logics; and decoupling initiatives to answer 'in parallel' to different pressures. Therefore, the paper contributes to the CSR literature investigating the relevance of the concept of institutional logics for the topic and can also support managers in shaping CSR strategy.